Merumuskan Pemikiran Ekonomi Muslim Tentang Rasionalitas dalam Perilaku Konsumen - Lia Istifhama (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2015)
Rationality is the characteristic of any action, belief, or desire,that makes their choice optimal under a set of constraints. It is a normativeconcept of reasoning in the sense that rational people should deriveconclusions in a consistent way given the information at disposal. It refers tothe conformity of one's beliefs with one's reasons to believe, or with one'sactions with one's reasons for action. However, the term "rationality" tendsto be used differently in different disciplines, including specializeddiscussions of economics, sociology, psychology, evolutionary biology andpolitical science. A rational decision is one that is not just reasoned, but isalso optimal for achieving a goal or solving a problem.